Media and Communication Responses to Rural Education in Taraba State, Nigeria: Education Planning and Management as Pathways for Protecting Vulnerable Children - Sharifatu Gago Ja’afaru; Livinus Jesse Ayih; Abdullahi Muhammad Yakub (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This study examined media and communication responses to rural education in Taraba State, Nigeria, with particular attention to how educational planning and communication strategies support the protection of vulnerable children. The problem addressed is the persistent exclusion of rural children from basic education despite policy interventions, largely due to weak communication systems, limited community engagement, and poor coordination between education planners, media platforms, and local stakeholders. These gaps continue to sustain high levels of out-of-school children, especially in underserved and crisis-affected communities. The study adopted a survey research design, using a structured questionnaire administered to 400 respondents drawn from parents, teachers, community leaders, and education administrators across the three senatorial districts of Taraba State. A total of 381 valid responses were analyzed using descriptive statistics, including frequency counts, percentages, and mean scores. Findings show that awareness of education-related campaigns is generally high (mean ≥ 3.70), with radio (mean = 3.95), community meetings (mean = 3.84), and faith-based organizations (mean = 3.79) emerging as the most dominant channels of information dissemination. Traditional and community-based communication strategies, particularly radio jingles (mean = 3.86) and town hall engagements (mean = 3.79), were found to be more effective than digital platforms such as SMS (mean = 2.40) and newspapers (mean = 2.53). Results further indicate that structured engagement strategies, especially parent–teacher meetings (mean = 3.84) and community volunteer initiatives (mean = 3.72), significantly enhance participation in rural education programmes and strengthen perceived protection for vulnerable children. The study concludes that rural education outcomes in Taraba State are strongly influenced by the effectiveness of localized, culturally embedded communication systems rather than digital-only approaches. It recommends the institutional strengthening of community radio programming in local languages, formal integration of religious and traditional leaders into education communication planning, and the establishment of structured feedback systems between schools and communities to improve accountability and sustained enrolment of vulnerable children.